LaFe11.6Si1.4Hy/Sn magnetocaloric composites by hot pressing. (15th July 2016) - Zhang, Heng; Liu, Jian; Zhang, Mingxiao; Shao, Yanyan; Li, Yang; Yan, Aru
Abstract: We report on the microstructure, mechanical properties, magnetocaloric effect and thermal transfer performance of LaFe11.6 Si1.4 Hy /Sn composites prepared by hot pressing. The liquid Sn forms a homogenous continuous matrix but does not react with LaFe11.6 Si1.4 Hy grains during compacting. By controlling pressing temperature, a set of composites combined high entropy change values of 10–13 J/kg K at 2 T with high thermal conductivity of about 7 W/mK has been obtained in a magnetostructural transition range of 1–17 °C. Graphical abstract: